Bosutinib, an SRC inhibitor, induces caspase‐independent cell death associated with permeabilization of lysosomal membranes in melanoma cells. (28th March 2017) - Noguchi, S.; Shibutani, S.; Fukushima, K.; Mori, T.; Igase, M.; Mizuno, T.
Abstract : Background: SRC kinase (SRC proto‐oncogene, non‐receptor tyrosine kinase) is a promising target for the treatment of solid cancers including human melanoma. Bosutinib (Bosu), a SRC inhibitor, has already been applied to the treatment of human chronic myelogenous leukemia and also has been assessed its safety in dogs. Aim: The aim of this study was to clarify a novel anti‐tumour mechanism of Bosu in canine and human melanoma cells. Materials and Methods: The canine and human melanoma cells were treated with Bosu and its effects were evaluated by the cell viability, the protein expression levels such as caspase‐3 and LC3, Annexin V/Propidium iodide staining, and confocal immunostaining. Results: Bosu induced the massive caspase‐independent cell death, and blocked autophagy flux, which resulted from lysosomal dysfunction. Lysosomal dysfunction caused by Bosu was due to lysosomal membrane permeabilization (LMP), which resulted in the release of lysosomal hydrolases including cathepsin B. Conclusion: Our data suggest that Bosu induces the cell death through induction of LMP in melanoma cells and is a promising therapeutic agent for treatment of melanoma in both dogs and humans.